Persepsi Peternak Terhadap Kinerja Penyuluh di Desa Nunmafo Kecamatan Insana Kabupaten Timor Tengah Utara - Kriatiani A.L Tahuk; Ture Simamora (JURNAL PERTANIAN, 2025)
This study aims to determine the characteristics of livestock farmers in Nunmafo Village, Insana District, North Central Timor Regency and to determine the perceptions of livestock farmers towards the performance of extension workers in Nunmafo Village, Insana District, North Central Timor Regency. This study was conducted from August to September 2024 in 3 farmer groups that are still active in Nunmafo Village. The population in this study was all Farmer Groups in Nunmafo Village, while the sample in this study was 60 respondents with a sampling technique using the census method. The type of data analysis in this study is descriptive percentage data analysis, with data collection techniques carried out through distributing questionnaires in the form of a Likert scale, observation, interviews, and recording. The results of the study showed that the characteristics of farmers based on age were dominated by the productive age category with ages ranging from 15 to 65 years with a percentage of 83.4%, at the farmer level it was very low, because some farmers only had elementary school education, while for livestock ownership > 3 heads and below with a percentage of 93%, with livestock experience of more than 10 years. The results of this study showed that the average responsiveness value was 72.3%, responsibility was 86.7% and quality of service was 5,68% where farmers were satisfied with the performance of extension workers. The results of the study showed that farmers' perceptions of extension materials, methods and media were in accordance with the needs of farmers, with an average of 86.67%.